Motif Gaya Bermedia Sosial Gen Alpha Di Instagram (Studi Fenomenalogi Mengenai Motif Dibalik Tren Menutupi Wajah) - Deby Febiola Putri (CV. ITTC INDONESIA, 2025)
This study explores the motives behind Generation Alpha's social media behavior on Instagram, particularly the emerging trend of covering their faces in photo uploads. This phenomenon reflects a new form of self-expression in the digital era, where Gen Alpha those born after 2010 grow up fully immersed in technology. Instagram is not only used for communication but also as a platform to construct personal identity and social presence.Using Alfred Schutz’s phenomenological approach, this research aims to understand the subjective meanings behind the act of face-covering by analyzing both “because motives” (past experiences) and “in-order-to motives” (intentional goals). Data was collected through in-depth interviews with key informants Gen Alpha individuals who actively use Instagram. The findings reveal that the main motives include a desire for privacy, aesthetic trends, and indirect forms of self-expression. Additionally, this behavior is influenced by their digital social environment, such as peers and influencers. This study contributes to the understanding of visual communication and digital lifestyle patterns among today’s young generation.